Methotrexate‐associated proliferative disorder in the lower esophagus extending to the gastroesophageal junction: A case report. Issue 1 (15th August 2021) - Hojo, Yuki; Takatsuna, Masafumi; Ikarashi, Satoshi; Kamimura, Hiroteru; Kimura, Rika; Mito, Masaki; Watanabe, Yusuke; Tani, Yusuke; Yokoyama, Junji; Terai, Shuji
Abstract: A 64‐year‐old woman was receiving oral methotrexate (MTX) for rheumatoid arthritis (RA) for 15 years. She underwent esophagogastroduodenoscopy because of discomfort in the chest. Endoscopic findings revealed an ulcer in the lower esophagus extending to the gastroesophageal junction (EGJ). The ulcer occupied half of the esophageal lumen and had a sharp and clear margin. Magnifying narrow‐band imaging endoscopy revealed the deposition of white plaque, and there were few microvessels in the edge and bottom of the ulcer. Histologic examination of the biopsy specimens from the oral edge of the lesion revealed proliferation of atypical lymphoid cells (immunophenotype results: CD20 [+], CD3 [partially +], CD5 [−], and BCL‐2 [−]]. The patient was diagnosed with methotrexate‐associated lymphoproliferative disorder (MTX‐LPD) and was advised to stop MTX intake. After 2 months of stopping MTX, the ulcer was found to be almost regressed and showed signs of healing. MTX‐LPD in the lower esophagus extending to the EGJ is extremely rare. This case can help in expanding the understanding of esophageal MTX‐LPD.